Model niat berperilaku melibatkan citra merk dan kepercayaan dalam niat pembelian produk fashion secara online pada Generasi Milenial di Kota Batam - Asnani; Riki (Bahtera Inovasi, 2024)
This study aims to analyze the role of brand image on purchase intention mediated by trust. This research uses quantitative research methods. The population used in this study is the millennial generation who have purchased fashion products online in Batam City. The technique used in sampling this research is purposive sampling, namely the selection of samples selected based on consideration of convenience sampling techniques, where the sampling technique by sampling by chance which is considered as a sample member is people who are easy to meet, are at the right time, and are easy to reach. The criteria are the millennial generation who have purchased fashion products through e-commerce platforms in Batam who were born around 1980 to 1995 when technology was advanced. Data analysis used descriptive analysis, outer model analysis, inner model, and mediating hypothesis testing through the SmartPLS programme. The results showed that brand image has a significant effect on trust, trust has a significant effect on purchase intention, while brand image has no significant effect on purchase intention, but trust is able to mediate between brand image and purchase intention